Roles of cell surface components of Escherichia coli K-12 in bacteriophage T4 infection: interaction of tail core with phospholipids. - Furukawa, H (1982)
The cell surface of Escherichia coli K-12, reconstituted from the OmpC protein, lipopolysaccharide, and the peptidoglycan layer, was active as a receptor for phage T4, resulting in the contraction of the tail sheath and the penetration of the core through the cell surface (Furukawa et al., J. Bacteriol. 140:1071--1080, 1979). In the present work the process of DNA ejection from the contracted T4 phage particle was studied. Contracted phage particles were adsorbed to phospholipid liposomes by the core tip. This adsorption resulted in ejection of phage DNA. Either phosphatidylglycerol or cardiolipin was active for the DNA ejection. A proton motive force across the liposome membrane was not required for these processes. The process of DNA ejection, however, was temperature dependent, whereas the adsorption of the core tip to liposomes took place at 4 degrees C. Based on these observations together with those in the previous paper, the process of T4 infection of E. coli K-12 cells is discussed with special reference to the roles of cell surface components.